Fostering Teacher Well-being in the University (Scholars' Journal, 2022)
The study aims at finding out the existing situation of wellbeing of the teachers at the Far Western university and its impact on teaching and learning environment. The research has also attempted to find out the solution of the poor wellbeing status of the teachers. The research is based on the information collected from four university level teachers teaching in different faculties of the university selected through purposive random sampling procedure. Open ended questions were used to elicit the emic view of the informants in the issue in the question. The major cause of the poor well being is the indifference that is shown by the authorities’ of the university. Similarly other causes that affect the well-being is academic calendar and the workload; issues related to the students. To foster the well being of the teachers the study revealed that the planning should be done in advance by the respective authorities and should communicate on time to the concerned. Similarly the collaboration among the teachers is also very important to maintain the wellbeing among teachers.